Safety and efficacy of live attenuated serine protease Vibrio harveyi (MVh_vhs) vaccine against vibriosis in Asian seabass [Lates calcarifer (Bloch, 1790)] - Chin, Yong Kit (2019)
Vibrio species is bacteria that cause natural outbreak of Vibriosis in marine aquaculture and cause the serious economic loss indirectly particularly in the early development of farmed fishes’ species. Live attenuated serine protease V. harveyi (MVh_vhs) was developed previously as vaccine candidate for farmed fishes against V. harveyi. In the first study, the gnotobiotic Artemia franciscana was used to evaluate the safety and efficacy of the newly developed live attenuated vaccine. The high concentration of MVh_vhs at concentration of 10⁹ CFU/mL is safe and had improved the Artemia larvae survival. It is also indicated that 10⁹ CFU/mL of MVh-vhs with 24 hours incubated Artemia larvae contributed higher survival at 36 h against multiple Vibrio challenge. Thus, we concluded that the incubation time affected bacterial concentration uptake by Artemia larvae and affect the effectiveness of Artemia bioencapsulation for targeted hosts. Skin abrasion often occurs in farmed fish following labour handling, injury by farm facilities, cannibalism and ectoparasites. In the second study, the Asian seabass (Lates calcarifer) fingerling was chosen as model to describe the effect of skin abrasion on the infectivity of V. harveyi on Asian seabass fingerling and compared to bacterial load and fish survival following immersion challenge before vaccination. No mortality was observed in control and non-skin abraded. However, fish of skin abraded group that were exposed to 10⁷ and 10⁸ CFU/mL of live V. harveyi showed 100% mortality by 96 h and 120 h, respectively. Infected fish of skin abraded group were classified into three stages: mild, moderate and severe infection. High bacterial loads were recorded for the severely infected dead fish, compared to low loads in moderately infected fish. Significantly higher bacterial load was recorded in the intestine, liver and gills of the severely infected dead fish. The findings revealed that skin injury causes Asian seabass fingerling to be more susceptible to V. harveyi infection. The study showed the lethal dose (LD50) of live V. harveyi on skin abraded Asian seabass fingerling for Vibrio challenged was determined at 10⁶.⁸³≈10⁷ CFU/mL. In the third study, the bath vaccination was chosen to be applied with the formalin killed V. harveyi and MVh_vhs for immunization of the Asian seabss fingerling model to investigate the immune related gene expressions. The high expression of chemokine ligand 4 (CCL4) and major histocompatibility complex I (MHC I) in the fish skin indicated the MVh_vhs induced mucosal innate and adaptive immunity while high expression of CCL4 and MHC I in the fish liver indicated the MVh_vhs, induced internal innate and adaptive immunity. After immersion challenge of wildtype V. harveyi with skin-abrasion on the vaccinated Asian seabass fingerling model, MVh_vhs contributed high survival indicated more than 50% survival for the fingerlings compared with formalin-killed V. harveyi and control at 120 h. The results indicated that the MVh_vhs can be applied through low cost and feasibly of bath vaccination to protect early protection of marine farmed fishes from natural occurrence of vibriosis.